KERUNTUHAN PROGRESIF GEDUNG BERATURAN SISTEM GANDA - Dhika Fazrian; Zulfikar Djauhari; Ridwan Ridwan (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2019)
Abstract: This research aimed to examine the progressive collapse of dual system building structures due to the loss of one or more structural elements that lead to successive collapse of other elements. Three cases of building structures were analyzed in this study using finite element software. Several columns on the first floor of the structure was removed and then the analysis was conducted to each structure until the progressive collapse existed. The nonlinear statics analysis was used to examine the location of the critical column while the linear statics analysis was carried out to find the demand capacity ratio, the bending moment ratio and robustness indicator as suggested by GSA 2003 and SNI 2847-2013. The results showed that the structure denoted in case 1 and case 2 that was loaded comply with GSA 2003 experienced the progressive collapse. On the other hand this phenomenon did not appear on the structure that was loaded in accordance with SNI 2847-2013. Furthermore, there was an increase in the bending moment capacity of the column/beam on all cases that were loaded comply with SNI 2847-2013 and GSA 2003. Robustness indicator is almost equal one with the type of progressive collapse is pancake collapse type. Abstrak: Penelitian ini bertujuan mengkaji keruntuhan progresif struktur gedung beraturan sistem ganda akibat hilangnya salah satu atau lebih elemen struktur yang menyebabkan keruntuhan secara beruntun elemen yang ada didekatnya. Tiga kasus struktur bangunan dianalisis dalam penelitian ini dengan menggunakan perangkat lunak berbasis elemen hingga. Beberapa kolom di lantai petama pada struktur dihilangkan dan dianalisis hingga struktur mengalami keruntuhan progresif. Analisis statik nonlinier digunakan untuk menge-tahui bagian kolom kritis dan analisis statik linier untuk mengetahui nilai rasio kapasitas, momen lentur, dan ketahanan batas sesuai dengan kriteria GSA 2003 dan SNI 2847-2013. Kesimpulannya adalah terjadi keruntuhan progresif sesuai kriteria GSA 2003 pada kasus 1 dan kasus 2. Sedangkan untuk kriteria SNI 2847-2013 tidak terjadi keruntuhan progresif. Terjadi peningkatan momen lentur pada setiap kasus sesuai kriteria GSA 2003 maupun SNI 2847-2013 dan nilai ketahanan batas mendekati satu dengan tipe keruntuhan progresif adalah pancake.